2014
DOI: 10.1007/s11606-014-3089-1
|View full text |Cite
|
Sign up to set email alerts
|

Why do People Avoid Medical Care? A Qualitative Study Using National Data

Abstract: BACKGROUND: Many studies have examined barriers to health care utilization, with the majority conducted in the context of specific populations and diseases. Less research has focused on why people avoid seeking medical care, even when they suspect they should go. OBJECTIVE: The purpose of the study was to present a comprehensive description and conceptual categorization of reasons people avoid medical care. DESIGN: Data were collected as part of the 2008 Health Information National Trends Survey, a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
206
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(249 citation statements)
references
References 55 publications
14
206
0
6
Order By: Relevance
“…An additional concerning finding with public health implications was that participants in our study reported delaying medical presentation for their breast symptom due to a "fear of not being able to afford treatment". This is consistent with recent results reported by Taber et al [41] , which found "high cost" and "lack of health insurance" to be reasons why patients reported avoiding medical care. This phenomenon may create an even greater burden in cancer patients, as a delay in presentation may translate to more costly treatment plans that may be even more expensive for the patient.…”
Section: Discussionsupporting
confidence: 93%
“…An additional concerning finding with public health implications was that participants in our study reported delaying medical presentation for their breast symptom due to a "fear of not being able to afford treatment". This is consistent with recent results reported by Taber et al [41] , which found "high cost" and "lack of health insurance" to be reasons why patients reported avoiding medical care. This phenomenon may create an even greater burden in cancer patients, as a delay in presentation may translate to more costly treatment plans that may be even more expensive for the patient.…”
Section: Discussionsupporting
confidence: 93%
“…Patients who are subject to a higher cost of care could suffer from increased economic hardships given that their income is being spent on health care instead of other necessities . Patients are likely to refuse medical care if the cost is too high, which would lead to increased disease severity, complications, and earlier‐than‐anticipated mortality . Given the effect of health‐care cost on patients and society, interventions to promote high‐value, cost‐conscious care have been instituted in the United States, such as the Centers for Medicare and Medicaid nonpayment policy for health care‐acquired conditions .…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding national recommendations and health promotion programs, French university students underuse health care services, with 20% not consulting a health professional (general practitioner or specialist) during their university years [3]. A small number of international studies have examined why young people avoid and delay medical care [4], providing a conceptual categorization of three main barriers: low perceived need to seek medical care; traditional barriers to medical care such as high cost, absence of health insurance, and time constraints; and lack of knowledge concerning the organization of the health care system and its services [5]. A study conducted on 41,000 French university students reported that: 23% of the participants did not feel the need to seek medical care, 13% did not have time for medical consultations, and 12% had economic difficulties to access and pay for health care services [3].…”
Section: Introductionmentioning
confidence: 99%